2017
DOI: 10.1093/cid/cix461
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Tests for Influenza, Respiratory Syncytial Virus, and Other Respiratory Viruses: A Systematic Review and Meta-analysis

Abstract: Rapid diagnosis of respiratory virus infections contributes to patient care. This systematic review evaluates the diagnostic accuracy of rapid tests for the detection of respiratory viruses. We searched Medline and EMBASE for studies evaluating these tests against polymerase chain reaction as the reference standard. Of 179 studies included, 134 evaluated rapid tests for influenza viruses, 32 for respiratory syncytial virus (RSV), and 13 for other respiratory viruses. We used the bivariate random effects model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
122
1
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(135 citation statements)
references
References 35 publications
6
122
1
6
Order By: Relevance
“…The use of rapid diagnostic influenza tests in the study setting would help to distinguish influenza from other febrile infections and would identify the causative agent for the substantial number of hospitalized SARI cases, which otherwise remain undiagnosed. However, rapid diagnostic influenza tests have shown low sensitivities in a recently published meta‐analysis and therefore must be interpreted with caution …”
Section: Discussionmentioning
confidence: 99%
“…The use of rapid diagnostic influenza tests in the study setting would help to distinguish influenza from other febrile infections and would identify the causative agent for the substantial number of hospitalized SARI cases, which otherwise remain undiagnosed. However, rapid diagnostic influenza tests have shown low sensitivities in a recently published meta‐analysis and therefore must be interpreted with caution …”
Section: Discussionmentioning
confidence: 99%
“…Because patients testing positive by Sofia® did not undergo further testing, we could not determine the true sensitivity and specificity of this test compared to FilmArray®. Previous studies have shown Sofia® specificity to be high, with a recent meta-analysis reporting a pooled specificity of 95.3% but sensitivity of only 75.3% for influenza A & B, and pooled specificity of 97.8% and sensitivity of 80% for RSV (Bruning et al, 2017;Gomez et al, 2015;Hazelton et al, 2015;Noh et al, 2015). Similarly, we assumed that all patients testing negative by PCR were true negatives; it is possible that some of these patients could have had false negative tests, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The Sofia® Fluorescent Immunoassay is a rapid, relatively inexpensive lateral flow assay for influenza A and B. It is reported to have a high specificity (94-98.3%) but low sensitivity (72.4-74%) compared to molecular assays (Bruning et al, 2017;Gomez et al, 2015;Hazelton et al, 2015;Noh et al, 2015). It requires less than 5 minutes hands-on setup time and has a 10-15 minute run-time.…”
Section: Laboratory Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Amplification curves were re-evaluated and all exhibited low-fluorescence, which could result in ambiguous interpretation. It is not uncommon that multiplex syndromic PCR panels are less sensitive compared to well-established LDT assays [17,18]. These syndromic panels often are dependent on uniformed nucleic acid isolation and PCR procedures, which are a trade-off between sensitivity and consolidation.…”
Section: Discussionmentioning
confidence: 99%